THU0202 Comparative effectiveness of tocilizumab as monotherapy versus tnf inhibitors in combination with conventional synthetic disease modifying antirheumatic drugs in bio-naÏve patients with rheumatoid arthritis. (12th June 2018) - Lauper, K.; Kvien, T.K.; Codreanu, C.; Hernández, M.V.; Ianonne, F.; Kristianslund, E.K.; Lukina, G.; Nordström, D.C.; Pavelka, K.; Rotar, Z.; Santos, M.J.; ,; et al.
Abstract : Background: Tocilizumab (TCZ) as monotherapy was more efficacious than the TNF inhibitor (TNFi) adalimumab as monotherapy for treatment of rheumatoid arthritis (RA) patients refractory to methotrexate (MTX) or in whom MTX was deemed inappropriate (ADACTA study). 1 However, data are lacking regarding the comparative real life effectiveness of TCZ as monotherapy versus TNFi combined with conventional synthetic DMARDS (csDMARDs). Objectives: To analyse treatment effectiveness by comparing drug retention rates and disease activity level in RA patients naïve to biological DMARDs (bDMARDs) treated with TCZ as monotherapy (TCZ mono) or TNFi combined with csDMARDs (TNFi combo). Methods: We included patients with RA across 10 European registries (TOCERRA collaboration) who were naïve to bDMARDs and received treatment with either TCZ mono or TNFi combo from 2009 to 2016. Drug retention rate was analysed using a Kaplan–Meier model. The proportions of patients reaching CDAI low disease activity (LDA) and remission after one year were adjusted for attrition with the LUNDEX index. 2 Results: A total of 6315 patients were eligible, 253 on TCZ mono and 6062 on TNFi combo. Patients with TCZ mono were younger, smoked less, and used less glucocorticoids at baseline compared with TNFi combo patients (table 1). The crude median retention was 2.8 years (95% CI: 2.0–3.3) and 2.0 years (95% CI: 1.8–2.1) for TCZ mono and TNFi combo, respectively (p=0.21). At 1 year, the rates of LUNDEX corrected CDAI LDA (CDAI ≤10) and remission (CDAI ≤2.8) were similar between both groups (figure 1). The results were unchanged when considering the type of combination with csDMARDs and the dosage of MTX. Conclusions: In routine care across 10 European countries, the retention and proportion of RA patients in LUNDEX corrected CDAI LDA and remission at 1 year were similar if treated with TCZ mono or TNFi combo. References: [1] Gabay C, et al. Lancet2013;381:1541–50. doi:10.1016/S0140-6736(13)60250-0 [2] Kristensen LE, et al. Arthritis Rheum2006;54:600–6. doi:10.1002/art.21570 Disclosure of Interest: K. Lauper: None declared, T. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB, Consultant for: AbbVie, BMS, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Orion Pharma, Pfizer, Roche, Sandoz and UCB, C. Codreanu: None declared, M. Hernández: None declared, F. Ianonne: None declared, E. Kristianslund: None declared, G. Lukina Consultant for: BMS, Roche, MSD, AbbVie and Pfizer, D. Nordström Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB, Consultant for: AbbVie, BMS, MSD, Roche, UCB and Pfizer, K. Pavelka Grant/research support from: AbbVie, Roche, Medis, MSD and Pfizer, Consultant for: AbbVie, Roche, Amgen, MSD, BMS, UCB and Egis, Z. Rotar: None declared, M. Santos: None declared, S. Gale Employee of: Genentech, M. John Employee of: F. Hoffmann-La Roche, Y. Luder Employee of: F. Hoffmann-La Roche, D. Courvoisier: None declared, C. Gabay Grant/research support from: Roche, AbbVie, MSD and Pfizer, Consultant for: AbbVie, BMS, Roche, Pfizer, Celgene, MSD, Janssen Cilag, Amgen, UCB